2010
DOI: 10.1136/jech.2010.112490
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and mortality in New Zealand: cohort study

Abstract: BackgroundFew cohort studies of the health effects of urban air pollution have been published. There is evidence, most consistently in studies with individual measurement of social factors, that more deprived populations are particularly sensitive to air pollution effects.MethodsRecords from the 1996 New Zealand census were anonymously and probabilistically linked to mortality data, creating a cohort study of the New Zealand population followed up for 3 years. There were 1.06 million adults living in urban are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 28 publications
5
63
1
1
Order By: Relevance
“…In particular, the American Cancer Society (ACS) study (3) and the Six-Cities study (4) have been extensively reanalyzed confirming their initial findings (5)(6)(7)(8)(9). Associations with the air pollution mixtures experienced by populations in Europe (10)(11)(12)(13)(14)(15)(16) and worldwide (17)(18)(19)(20) have also been reported.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In particular, the American Cancer Society (ACS) study (3) and the Six-Cities study (4) have been extensively reanalyzed confirming their initial findings (5)(6)(7)(8)(9). Associations with the air pollution mixtures experienced by populations in Europe (10)(11)(12)(13)(14)(15)(16) and worldwide (17)(18)(19)(20) have also been reported.…”
mentioning
confidence: 82%
“…The following information was extracted from the electronic patient record and used to construct covariates: age; sex; smoking (non-, ex-, and current smoker, with further categories of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and 401 cigarettes per day); and body mass index (BMI) (,20, >20 and ,25, >25 and ,30, >30). The last recorded status before January 1, 2003 was used to code the variables, except for nonsmokers, who were reclassified as ex-smokers if they had older historical codes indicating smoking.…”
Section: Methodsmentioning
confidence: 99%
“…We identified 17 cohort studies Beeson et al 1998;Cao et al 2011;Carey et al 2013;Cesaroni et al 2013;Hales et al 2012;Hart et al 2011;Heinrich et al 2013;Jerrett et al 2013;Katanoda et al 2011;Krewski et al 2009;Lepeule et al 2012;Lipsett et al 2011;McDonnell et al 2000;Naess et al 2007;Pope et al 2002;Raaschou-Nielsen et al 2013) and one case-control study (Hystad et al 2013) of lung cancer that provided estimates of the quantitative relationships between the risk of lung cancer and exposure to PM 2.5 or PM 10 that could be expressed per 10-μg/m 3 change in PM. Estimates from one cohort study (Naess et al 2007) could not be converted to units of 10-μg/m 3 , and thus, this study did not contribute to the meta-estimates.…”
Section: Studies Includedmentioning
confidence: 99%
“…18 Yet the epidemiological explanation of this phenomenon is still insufficient. Some studies have found excess cancer mortality associated with higher doses of exposure to carcinogens in the urban environment, such as air pollution 8,19,20 and estrogenic compounds. 21,22 The major behavioral risk factors for cancer are known to be tobacco, alcohol, and diet and physical activity, 23 but there is still a lack of substantial epidemiological evidence that exposure to these risks or the causal effects of these risks are aggravated in urban areas.…”
Section: Discussionmentioning
confidence: 99%